2016
DOI: 10.1155/2016/9548302
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of High Voltage Insulators Made of Ceramic Using Spectrophotometry

Abstract: The paper presents results of comparative analysis of optical signals emitted by partial discharges occurring on three types of high voltage insulators made of porcelain. The research work consisted of diagnosis of the following devices: a long rod insulator, a cap insulator, and an insulating cylinder. For optical signal registration a spectrophotometer was applied. All measurements were performed under laboratory conditions by changing the value of partial discharges generation voltage. For the cylindrical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Parallel to these activities, research was also carried out in the field of basic studies aimed at learning new possibilities of using the physicochemical properties of electrical discharge forms [5][6][7][8][9][10]. Examples of not fully understood areas are X-ray radiation and optical radiation emitted by electrical discharges [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to these activities, research was also carried out in the field of basic studies aimed at learning new possibilities of using the physicochemical properties of electrical discharge forms [5][6][7][8][9][10]. Examples of not fully understood areas are X-ray radiation and optical radiation emitted by electrical discharges [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the analyses, it was concluded that the spectral intensity curves are similar for all types of power transmission lines. Furthermore, the shapes of the registered spectra resemble those obtained by spectrophotometry during emission of surface discharges on bushing and support insulators [13][14][15] and on insulators made of porcelain and glass [16,17]. The occurrence of particular wavelengths changes for various generation voltages and distances d; however, no linear/monotonic relationships were found.…”
Section: Discussion Of Analysis Resultsmentioning
confidence: 68%
“…The value is being saved to database, and the generation of higher voltage continues until breakdown is achieved. It is possible to measure earlier (lower voltage value) and more accurate by using UV corona discharge camera like Ofil DayCor SuperB or spectrophotometer [6,7]. Using the OE method is part of future research of this study.…”
Section: Metrological Parameters Of the Measuring Systemmentioning
confidence: 99%
“…This involves shutting off power supply for the device during connection/disconnection of probes which is a huge disadvantage [3]. Non-invasive methods include: acoustic emission [4,5], optical emission [6,7], electromagnetic or radio-frequency detection [8,9]. This paper concerns the use of invasive, classical method.…”
Section: Metrological Parameters Of the Measuring Systemmentioning
confidence: 99%